Karakteristik Introvert: Analisis Pandangan Susan Cain (Jurnal Bimbingan dan Konseling Islam, 2022)
Analysis of Introvert Characteristics According to Susan Cain’s View and Its Relevance to QS. Ar-Ra’du Verse 11. This study aimed to determine the characteristics of introverts according to Susan Cain’s view and its relevance to QS. Ar-Ra’du verse 11, and also the implementation of existing Islamic counseling values. This research used qualitative method with content analysis approach. The primary source for this research was a book by Susan Cain entitled Quiet: The Power of Introverts in a World That Can’t Stop Talking. The results obtained from this study included: (1) An analysis of the characteristics of introverts that distinguish them from extroverts according to Susan Cain’s view can be divided into three categories, namely based on the level of external stimulus needed to function properly, work habits, and social style; (2) There is relevance between introverted characteristics and QS. Ar-ra’du verse 11; (3) Implementation of counseling values that can be taken from this research, namely the values of gratitude, tolerance, and endeavor